2016
DOI: 10.21276/aanat.2016.2.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Variant Anatomy of the Jugular Foramen: An Osteological Study

Abstract: Background: Jugular foramen lesions are among the major complications of skull base surgery. Morphological variations in the structure are pertinent during interpretation of skull base radiographs and in surgical procedures within the foramen. This study therefore aimed at describing the morphology of the jugular foramen in a Kenyan population. Methods: One hundred and five adult skulls from the Nairobi National Museums were used. Jugular foramen septation, dome and dimensions were studied extracranially. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies have shown that indeed Kenyans have a larger IJV than other populations. 15 This might therefore explain the predominant medial relation of the SAN in our setting.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have shown that indeed Kenyans have a larger IJV than other populations. 15 This might therefore explain the predominant medial relation of the SAN in our setting.…”
Section: Discussionmentioning
confidence: 78%